2010
DOI: 10.1017/s1740925x10000165
|View full text |Cite
|
Sign up to set email alerts
|

Bergmann glial ensheathment of dendritic spines regulates synapse number without affecting spine motility

Abstract: In the cerebellum, lamellar Bergmann glial (BG) appendages wrap tightly around almost every Purkinje cell dendritic spine. The function of this glial ensheathment of spines is not entirely understood. The development of ensheathment begins near the onset of synaptogenesis, when motility of both BG processes and dendritic spines are high. By the end of the synaptogenic period, ensheathment is complete and motility of the BG processes decreases, correlating with the decreased motility of dendritic spines. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…A single mouse cortical astrocyte is estimated to contact over 100,000 synapses; whereas a human astrocyte can contact up to 2,000,000 synapses (Bushong et al, 2002; Oberheim et al, 2009). A similar tile-like organization of other astrocyte-like radial glia cells have also been observed for cerebellar Bergmann glia, which ensheath Purkinje cell synapses, and retinal Muller Glia, which ensheath synapses within the inner and outer plexiform layers (Lippman Bell et al, 2010; Lippman et al, 2008; Wang et al, 2017). These observations indicate that astrocytes, through their fine processes, have the ability to sense and adhere to synapses and coordinate with the neighboring astrocytes to tile and completely cover the neuropil.…”
Section: Astrocytes Are Integral Components Of Synapsessupporting
confidence: 65%
“…A single mouse cortical astrocyte is estimated to contact over 100,000 synapses; whereas a human astrocyte can contact up to 2,000,000 synapses (Bushong et al, 2002; Oberheim et al, 2009). A similar tile-like organization of other astrocyte-like radial glia cells have also been observed for cerebellar Bergmann glia, which ensheath Purkinje cell synapses, and retinal Muller Glia, which ensheath synapses within the inner and outer plexiform layers (Lippman Bell et al, 2010; Lippman et al, 2008; Wang et al, 2017). These observations indicate that astrocytes, through their fine processes, have the ability to sense and adhere to synapses and coordinate with the neighboring astrocytes to tile and completely cover the neuropil.…”
Section: Astrocytes Are Integral Components Of Synapsessupporting
confidence: 65%
“…It is generally known that glial cells including astrocytes tightly wrap synapses from the post-synaptic side in brain tissues51. In the hippocampus of mature animals, approximately 57% of synapses are sheathed.…”
Section: Discussionmentioning
confidence: 99%
“…Very fine, and apparently highly mobile, astrocytic processes have been reported in organotypic brain slices using a membrane‐bound GFP (Benediktsson et al, 2005). Furthermore, co‐labeling of dendritic spines and PAPs in hippocampal (Halassa et al, 2007a; Perez‐Alvarez et al, 2014; Verbich et al, 2012) and cerebellar slices (Lippman Bell et al, 2010; Lippman et al, 2008) as well as in vivo (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014) suggested that PAPs are highly dynamic structures that engage and disengage with dendritic spines, also responding to the induction of synaptic plasticity (Bernardinelli et al, 2014b; Perez‐Alvarez et al, 2014). …”
Section: Current Methods To Monitor Fine Astrocyte Morphology: Promismentioning
confidence: 99%
“…Furthermore, blocking Rac‐1 and interfering with PAP motility leads to enhanced number of dendritic filopodia (Nishida and Okabe, 2007). Similarly, in the cerebellum Bergmann glia coverage is required for synapse stabilization and regulation (Lippman Bell et al, 2010; Lippman et al, 2008). …”
Section: Regulating Synaptic Morphogenesis Through Paps?mentioning
confidence: 99%